Pre-sowing treatment of acorns with gibberellic acid and N-hexanoyl-L-homoserine lactone induced changes in growth and hormonal balance of Quercus robur L. seedlings - Voytenko Lesya; Vasyuk Valentyna; Babenko Lidia; Shcherbatiuk Mykola; Romanenko Kateryna; Kosakivska Iryna V. (Metsanduslikud Uurimused)
This study aimed to assess and compare the impact of priming with gibberellic acid (GA3) and N-hexanoyl-L-homoserine lactone (C6-HSL) on acorn germination, seedling growth, and the balance of endogenous phytohormones in 47-day-old seedlings of pedunculated oak (Quercus robur L.). We hypothesized that exogenous GA3 and C6-HSL induce changes in hormonal homeostasis, which activate the germination of acorns and growth of seedlings. Acorns were soaked for 24 hours in water (control) and solutions of gibberellic acid (50 mg/L) and C6-HSL (300 ng/ml). The dynamics and distribution of endogenous cytokinins, abscisic (ABA), indole-3-acetic (IAA), gibberellic (GA3 and GA4) and salicylic (SA) acid in 47-day-old seedlings' organs of Q. robur were analysed using HPLC-MS. Priming with GA3 solution resulted in 85.8% of acorn germination, surpassing the control by 24.6%, whereas priming with C6-HSL solution led to 93.4% germination, surpassing the control by 32.2%. GA3-primed plants (GA3+plants) showed enhanced shoot growth, while C6-HSL-primed (C6-HSL+plants) plants had intensive root development. GA3 also caused epicotyl shoot thickening. Both regulators increased cytokinins, mainly active zeatin forms, with pronounced changes in shoots under C6-HSL and in roots under GA3. ABA content increased in both GA3+ and C6-HSL+plants, with a more significant effect in the roots of C6-HSL+plants. Both regulators negatively impacted IAA accumulation, with GA3 exhibiting a more pronounced effect, causing IAA accumulation to shift from shoots to roots post priming, whereas IAA dominance occurred in the shoots of non-primed acorns (C-plants) and C6-HSL+plants. The total gibberellin content increased in primed seedlings, with GA4 accumulating in GA3+plants and GA3 in C6-HSL+plants, surpassing GA3+plants by 40.7%. GA3+plants exhibited decreased SA in roots, contrasting with increased SA in the roots of C6-HSL+plants. In conclusion, both growth regulators optimized acorn germination, induced changes in hormonal homeostasis and enhanced seedling growth, with increased root growth in C6-HSL plants and shoot growth in GA3 plants.